Strategies to improve environmental hygiene and health in Gebang Mekar Village - Indriaty, Sulistiorini; Zamzam, Muhammad Yani; Pratami, Trysha Inka Lutfi; Alfara, Fauzan Agry; Elvaretha, Saskia; Rudyastuti, Shilvie Febian; Apriliani, Fiska; Azzahra, Nabilla; Fitriani, Indah; Lingga, Candra (Community Empowerment, 2025)
Gebang Mekar Village, Gebang Subdistrict, Cirebon Regency faces environmental hygiene and public health issues due to a lack of awareness regarding the importance of cleanliness and healthy lifestyles. This community service program aims to increase community awareness and participation in maintaining environmental hygiene and health. The community service program was conducted using socialization, discussion, and practical methods. JUMSIH was carried out by cleaning places of worship every Friday, TIMIMIMU introduced herbal drinks as healthy alternatives every Sunday, and PROKELING involved the community in joint environmental cleaning activities. Overall, the activities carried out successfully increased community awareness and understanding of environmental hygiene and health. Despite challenges in terms of limited resources and participation, positive impacts were seen through increased shared responsibility, understanding of the benefits of healthy lifestyles, and active participation in maintaining environmental cleanliness.